Pathological findings that contribute to tissue stiffness in the spleen of liver cirrhosis patients. Issue 12 (7th June 2018) - Kondo, Reiichiro; Kage, Masayoshi; Iijima, Hiroko; Fujimoto, Jiro; Nishimura, Takashi; Aizawa, Nobuhiro; Akiba, Jun; Naito, Yoshiki; Kusano, Hironori; Nakayama, Masamichi; Mihara, Yutaro; Tanigawa, Masahiko; et al.
Abstract : Aim: Spleen stiffness is increased in liver cirrhosis (LC). We attempted to characterize the pathological features of spleen in LC. Methods: We compared pathological findings of resected spleen tissues of 28 LC patients and those of six healthy controls. In addition, we measured spleen stiffness before splenectomy by shear wave elastography in nine LC patients. After splenectomy, we examined the relationship between spleen stiffness and pathological findings. Results: Passive congestion of the spleen was more frequently observed in LC patients than in controls ( P < 0.01). The sinus was wider in LC patients than in controls ( P < 0.01). In the spleens of the LC patients, diffuse α‐smooth muscle actin (αSMA) expression of sinusoidal mesenchymal cells and deposition of collagen fibers on the perisinusoidal wall were observed. In nine LC patients whose spleen stiffness was examined, the width of the sinus increased along with spleen stiffness ( r = 0.89, P < 0.01). Spleen stiffness was higher in the spleen tissues with diffuse αSMA expression of sinusoidal mesenchymal cells than in those with partial αSMA expression of sinusoidal mesenchymal cells ( P = 0.01). The degree of fibrosis was higher in the LC patients with diffuse αSMA expression of the red pulp than in those with partial αSMA expression of the red pulp ( P = 0.03). Conclusion: In the LC patients, spleen tissues showed passive congestion with a dilated sinus, diffuse αSMA expression of sinusoidal mesenchymal cells, and deposition of collagen fibers on the perisinusoidal wall. This contributed to spleen stiffness.